16S rRNA molecular analysis, phosphorus solubilization, and influence on the growth of soybean (Glycine max) and maize (Zea mays) by bacteria isolated from the soil - Eduardo Silva Almeida, Wallynson [UNESP]; de Souza, Jackson Antônio Marcondes [UNESP] (UNESP - Universidade Estadual Paulista, 2024)
Microorganisms play an active role in Phosphorus (P) transformations in the soil, influencing its availability to plants and its flux in nature. The transformations result from the decomposition and mineralization of organic compounds, immobilization in microbiomes, and solubilization of inorganic minerals. The basis of this study was to evaluate 10 bacterial isolates, aiming to characterize them as: growth pattern in TY medium (Tryptone Yeast); growth pattern on NBRIP medium (National Botanical Research Institute's Phosphate); solubilization of calcium hydroxide phosphate (Ca5(OH)(PO4)3); pH variation in different media; partial sequencing of the 16S rRNA gene, and influence of growth, in a greenhouse, for soybean (Glycine max) and maize (Zea mays) crops. Among the ten isolates, the best P solubilizers were LGA05-V0513, LGA06-V0517 (Bacillus cereus), and LGA14-V20J (Arthrobacter echigonensis), while the worst one was the isolate LGA08-V20C (Acinetobacter sp.). The main isolates that benefited the development of soybean and maize plants belong to the genus Bacillus.
Análise molecular 16S rRNA, solubilização do fostato e influência no crescimento de soja (Glycine max) e milho (Zea mays) por bactérias isoladas do solo
Keywords: Bacillus spp; pH acidification; Phosphorus-solubilizing bacteria (PSB); Plant growth-promoting rhizobacteria (PGPR)